Four questions to predict cognitive decline in de novo Parkinson’s disease - Jan Hlavnička; Josef Mana; Ondrej Bezdicek; Martin Čihák; Filip Havlík; Dominik Škrabal; Tereza Bartošová; Karel Šonka; Evžen Růžička; Petr Dušek (npj Parkinson's Disease)
Abstract Early identification of cognitive decline (CD) in de novo Parkinson’s disease (PD) is crucial for choosing appropriate therapies and recruiting for clinical trials. However, existing prognostic models lack flexibility, scalability and require costly instrumentation. This study explores the utility of standard clinical questionnaires and criteria to predict CD in de novo PD. A total of 186 patients from the Parkinson Progression Markers Initiative (PPMI) and 48 patients from the Biomarkers of Parkinson’s Disease project (BIO-PD) underwent clinical interviews, comprehensive tests, and questionnaires. A model based only on age of disease onset, history of stroke, history of fainting, and vocalization during dreams predicted CD in 2 and 4-year horizons with an area under curve (AUC) of 70% ± 10% standard deviation (cross-validated PPMI), 79% (overall PPMI), and 78% (validation in BIO-PD). This approach enables rapid preliminary screening using just four simple questions, achieving predictive accuracy comparable to instrumentation-based methods while reducing assessment time.